Functioning of a Verbal Predicate in the Artistic Style of Yakut Language - Ivanova, Sargylana Vladimirovna; Manchurina, Lidiya Egorovna (Journal of History Culture and Art Research, 2018)
In this article the verbal predicate functioning in the artistic style of the Yakut language is subjected to semantic-stylistic and stylo-statistical analysis. The authors consider artistic style’s rich language as one of the functional style varieties, which implies a comparative study of its language with the language of other styles of speech. As a result of analysis, the lexical-semantic and grammatical-semantic characteristics of verbal predicates are given as one of the main members of sentence that determine the symmetry of modal grammatical meanings specific to the artistic style. Also revealed quantitative indicators of verbal predicates of artistic style in close relationship with their qualitative characteristics. The theoretical and methodological basis of the study depend works of L.N. Kharitonov, E.I. Korkina, P.S. Afanas’ev, P.A. Sleptsov, N.E. Petrov, G.G. Filippov and others on various aspects of the studied problem. A semantic-stylistic method, stylo-statistical and comparative methods are applied in the study. The study reveals the frequency of the verbal predicate forms use in the artistic style, which allowed to objectively assess the indicators that were identified using the semantic-stylistic method. The comparative method contributed to reveal the stylistic originality of the artistic style in relation to other styles. The functioning of the verbal predicate in the artistic style depends on the grammatical semantics of some verb forms, as well as lexical-semantic nature of certain verbal predicates. Revealed the absolute superiority in quantitative terms of the analytical forms of the composite predicate expressed by the forms of the species, the past tense and mood. The stylistic power of composite predicate’s analytical forms lies in their semantic nature, which assumes the presence of all richness of diverse modal meanings of the syntactic means of the Yakut language.